SolCelSim: simulation of charge transport in solar cells developed in Comsol Application Builder. (4th July 2022) - Vieira, Joao A. T. P.; Cendula, Peter
ABSTRACT: A user-friendly software SolCelSim is introduced for the simulation of the charge transport in a solar cell with an arbitrary number of layers. Various recombination mechanisms, types of transport through internal layer interfaces and conditions at the contacts can be chosen. A wide range of the measurement methods available for the solar cells such as photocurrent-voltage, incident photon-to-current efficiency and impedance spectroscopy can be simulated with SolCelSim. Any parameter of the layers can be swept automatically during the simulation in order to obtain the dependence of the simulation results on the particular parameter values. Import/export buttons for the experimental/simulated data are provided to facilitate comparison between the measurements and simulations. The application provides a convenient entry-point for the experimentally oriented researchers in order to execute the drift-diffusion simulation of their solar cell devices. Furthermore, SolCelSim provides an example of advanced use of Comsol Application Builder in the development of complex Comsol applications with dynamic geometry, import/export and error handling features.